A Deeper Look at the Boy Scouts of America “Perversion” Files: Structural Factors Related to Access and Abuse - Mackinem, Mitchell B. (Journal of interpersonal violence, 2024)
The Boy Scouts of America’s (BSA’s) Ineligible Volunteer (IV) files, commonly called the “perversion files,” is a unique data set allowing researchers to examine organizational characteristics that allow for child sexual victimization. Despite the uniqueness of this data set, few researchers have examined it. The researchers examined a random sample of cases from the IV files of scout leaders who molested scouts. A situational crime theoretical model was employed as had been used in studies on the Catholic Church sexual abuse scandal, proving effective. The researchers examined randomly selected from 1980 to 1999. Of initially examined 400 randomly selected cases, only 140 held retrievable data. The majority of the 140 cases did not have scouting victims, which resulted in a reduction to 48 cases. Beyond the several scouting forms, many files contained public domain information, including newspaper articles, police reports, criminal justice records, and/or records of civil litigation. Through both the scouting documents and the public domain records, the researchers identified six BSA-specific characteristics that allowed motivated adult leaders to molest their victims. These characteristics included (a) weak or inefficient incident reporting system, (b) failure to collect and review pertinent information, (c) organizationally legitimate reasons for one-on-one contact, (d) volunteer imbalance, (e) legitimate reasons for separation from protective adults, and (f) social status as a prophylactic defense. These structural characteristics are explored through descriptive statistics and specific case studies illustrating the phenomena. When the history of the IV files came to light through litigation, the BSA was forced to reconcile its past actions and develop new preventive measures. The Boy Scouts of America implemented various actions to protect the youth. Many of these protections specifically address structural characteristics.